Assessment of combination of pretreatment of Sorghum durra stalk and production of chimeric enzyme (β-glucosidase and endo β-1, 4 glucanase, CtGH1-L1-CtGH5-F194A) and cellobiohydrolase (CtCBH5A) for saccharification to produce bioethanol. Issue 9 (1st October 2020) - Nedumaran, Mohanapriya; Singh, Shweta; Jamaldheen, Sumitha Banu; Nath, Priyanka; Moholkar, Vijayanand Suryakant; Goyal, Arun
Abstract: Optimization of pretreatment and saccharification of Sorghum durra stalk (Sds) was carried out. The chimeric enzyme ( Ct GH1-L1- Ct GH5-F194A) having β-glucosidase ( Ct GH1) and endo β-1, 4 glucanase activity ( Ct GH5-F194A) and cellobiohydrolase ( Ct CBH5A) from Clostridium thermocellum were used for saccharification. Chimeric enzyme will save production cost of two enzymes, individually. Stage 2 pretreatment by 1% (w/v) NaOH assisted autoclaving + 1.5% (v/v) dilute H2 SO4 assisted oven heating gave lower total sugar yield (366.6 mg/g of pretreated Sds) and total glucose yield (195 mg/g of pretreated Sds) in pretreated hydrolysate with highest crystallinity index 55.6% than the other stage 2 pretreatments. Optimized parameters for saccharification of above stage 2 pretreated biomass were 3% (w/v) biomass concentration, enzyme (chimera: cellobiohydrolase) ratio, 2:3 (U/g) of biomass, total enzyme loading (350 U/g of pretreated biomass), 24 h and 30 °C. Best stage 2 pretreated Sds under optimized enzyme saccharification conditions gave maximum total reducing sugar yield 417 mg/g and glucose yield 285 mg/g pretreated biomass in hydrolysate. Best stage 2 pretreated Sds showed significantly higher cellulose, 71.3% and lower lignin, 2.0% and hemicellulose, 12.2% (w/w) content suggesting the effectiveness of method. This hydrolysate upon SHF using Saccharomyces cerevisiae under unoptimized conditions produced ethanol yield, 0.12 g/g of glucose. Abbreviation: Ct-Clostridium thermocellum, Sds- Sorghum durra stalk, TRS-Total reducing sugar, HPLC-High performance liquid chromatography, RI-Refractive index, ADL-acid insoluble lignin, GYE-Glucose yeast extract, MGYP-Malt glucose yeast extract peptone, SHF-separate hydrolysis and fermentation, OD-Optical density, PVDF-Poly vinylidene fluoride, TS-total sugar, FESEM-Field emission scanning electron microscopy, XRD-X-ray diffraction, FTIR-Fourier transform infra-red spectroscopy and CrI -Crystallinity index.